Neural Information Processing 19th International Conference, ICONIP 2012, Doha, Qatar, November 12-15, 2012, Proceedings, Part I19th International Conference, ICONIP 2012, Doha, Qatar, November 12-15, 2012, Proceedings, Part IV - Huang, Tingwen; Zeng, Zhigang; Li, Chuandong; Leung, Chi Sing.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The five volume set LNCS 7663, LNCS 7664, LNCS 7665, LNCS 7666 and LNCS 7667 constitutes the proceedings of the 19th International Conference on Neural Information Processing, ICONIP 2012, held in Doha, Qatar, in November 2012. The 423 regular session papers presented were carefully reviewed and selected from numerous submissions. These papers cover all major topics of theoretical research, empirical study and applications of neural information processing research. The 5 volumes represent 5 topical sections containing articles on theoretical analysis, neural modeling, algorithms, applications, as well as simulation and synthesis.
Neural Network Learning for Blind Source Separation with Application in Dam Safety Monitoring -- Improved BTC Algorithm for Gray Scale Images Using K-Means Quad Clustering -- Optimization of a Neural Network for Computer Vision Based Fall Detection with Fixed-Point Arithmetic -- Customer Relationship Management Using Partial Focus Feature Reduction -- An Automated System for the Grading of Diabetic Maculopathy in Fundus Images -- An Iterative Method for a Class of Generalized Global Dynamical System Involving Fuzzy Mappings in Hilbert Spaces -- Estimation of Missing Precipitation Records Using Modular Artificial Neural Networks -- Office Employees Authentication Based on E-exam Techniques -- Obtaining Single Document Summaries Using Latent Dirichlet Allocation -- Object Recognition Using Sparse Representation of Overcomplete Dictionary -- PEAQ Compatible Audio Quality Estimation Using Computational Auditory Model.- A System for Offline Character Recognition Using Auto-encoder Networks -- TrafficS: A Behavior-Based Network Traffic Classification Benchmark System with Traffic Sampling Functionality -- Harmony Search with Multi-Parent Crossover for Solving IEEE-CEC2011 Competition Problems -- New Intelligent Interactive Automated Systems for Design of Machine Elements and Assemblies.- Neural Networks Based Aerial Images Segmentation Method -- Frontal Cortex Neural Activities Shift Cognitive Resources Away from Facial Activities in Real-Time Problem Solving -- Implement Real-Time Polyphonic Pitch Detection and Feedback System for the Melodic Instrument Player -- Classification of Interview Sheets Using Self-Organizing Maps for Determination of Ophthalmic Examinations -- Sound-Based Ranging System in Greenhouse Environment with Multipath Effect Compensation Using Artificial Neural Network -- Multimedia Educational Content for Saudi Deaf -- Grasping Region Identification in Novel Objects Using Microsoft Kinect -- Annotating Words Using WordNet Semantic Glosses -- Identification of Moving Vehicle Trajectory Using Manifold Learning -- Approaches for the Detection of the Keywords in Spoken Documents Application for the Field of E-Libraries.- Fast Affine Invariant Shape Matching from 3D Images Based on the Distance Association Map and the Genetic Algorithm -- Sparse Gradient-Based Direct Policy Search -- Application of Sampling Theory to Forecast Ozone by Neural Network -- Application of Genetic Neural Networks for Modeling of Active Devices -- Displacement Prediction Model of Landslide Based on Ensemble of Extreme Learning Machine -- Effective Handwriting Recognition System Using Geometrical Character Analysis Algorithms -- The Use of ASM Feature Extraction and Machine Learning for the Discrimination of Members of the Fish Ectoparasite Genus Gyrodactylus -- DBNs-BLR (MCMC) -GAs-KNN: A Novel Framework of Hybrid System for Thalassemia Expert System.- Hybrid Approach for Diagnosing Thyroid, Hepatitis, and Breast Cancer Based on Correlation Based Feature Selection and Na¨ıve Bayes -- Data Discretization Using the Extreme Learning Machine Neural Network -- Bayesian Variable Selection in Neural Networks for Short-Term Meteorological Prediction.- Integrated Problem Solving Steering Framework on Clash Reconciliation Strategies for University Examination Timetabling Problem.-  A Data Gathering Scheme in Wireless Sensor Networks Using a Spiking Neural Network with Simple Local Information -- Utilizing Symbolic Representation in Synergistic Neural Networks Classifier of Control Chart Patterns -- Semantic Analysis of FBI News Reports -- Regularized Signal Deconvolution Based on Hybrid Swarm Intelligence: Application to Neutron Imaging -- Artificial Bees Colony Optimized Neural Network Model for ECG Signals Classification -- Single-Trial Multi-channel N170 Estimation Using Linear Discriminant Analysis (LDA).- EEG Based Foot Movement Onset Detection with the Probabilistic Classification Vector Machine -- Neural Networks Based System for the Supervision of Therapeutic Exercises.- Fuzzy Model for Detection and Estimation of the Degree of Autism Spectrum Disorder -- Detecting Different Tasks Using EEG-Source-Temporal Features -- Artificial Neural Network Classification Models for Stress in Reading -- Performance Evaluation of TCP and UDP Traffic in IEEE 1451 Compliant Healthcare Infrastructure -- Power and Task Management in Wireless Body Area Network Based Medical Monitoring Systems -- Feature Salience for Neural Networks: Comparing Algorithms.- Adaptive Modeling of HRTFs Based on Reinforcement Learning -- Damage Pattern Recognition of Refractory Materials Based on BP Neural Network.- Robust and Optimum Features for Persian Accent Classification  Using Artificial Neural Network -- Identification of Factors Characterising Volatility and Firm-Specific Risk Using Ensemble Classifiers -- Fuzzy Classification-Based Control of Wheelchair Using EEG Data to Assist People with Disabilities.- EEG-Based Emotion Recognition in Listening Music by Using Support Vector Machine and Linear Dynamic System -- Analysis of Genetic Disease Hemophilia B by Using Support Vector Machine -- EEG-Based Fatigue Classification by Using Parallel Hidden Markov Model and Pattern Classifier Combination -- A Novel Approach to Protein Structure Prediction Using PCA or LDA Based Extreme Learning Machines.- Hierarchical Parallel PSO-SVM Based Subject-Independent Sleep Apnea Classification.- Air Quality Monitoring and Prediction System Using Machine-to-Machine Platform.- An Extension of the Consensus-Based Bundle Algorithm for Group Dependant Tasks with Equipment Dependencies -- From e-Learning to m-Learning: Context-Aware CBR System -- Extreme Learning Machines for Intrusion Detection Systems -- A Self-Organizing Maps Multivariate Spatio-temporal Approach for the Classification of Atmospheric Conditions -- An Online Signature Verification System for Forgery and Disguise Detection -- A Modular Approach to Support the Multidisciplinary Design of Educational Game Experiences -- Touch-Based Mobile Phone Interface Guidelines and Design Recommendations for Elderly People: A Survey of the Literature -- A Novel Paradigm for Mining Cell Phenotypes in Multi-tag Bioimages Using a Locality Preserving Nonlinear Embedding -- SNEOM: A Sanger Network Based Extended Over-Sampling Method. Application to Imbalanced Biomedical Datasets -- Abductive Neural Network Modeling for Hand Recognition Using Geometric Features -- Designing Serious Games for Adult Students with Cognitive Disabilities -- Neural Network Based Approach for Automotive Brake Light Parameter Estimation -- A Single Neuron Model for Pattern Classification -- Continuous Classification of Spatio-temporal Data Streams Using Liquid State Machines -- On the Selection of Time-Frequency Features for Improving the Detection and Classification of Newborn EEG Seizure Signals and Other Abnormalities -- Turf Grass Irrigation Using Neuro-Fuzzy System -- A Target-Reaching Controller for Mobile Robots Using Spiking Neural Networks -- Assessing Reliability of Substation Spare Current Transformer System -- Study on Supply Disruption Management of Supply Chain Based on Case-Based Reasoning -- Global Minimizer of Large Scale Stochastic Rosenbrock Function: Canonical Duality Approach -- Study on Landslide Deformation Prediction Based on Recurrent Neural Network under the Function of Rainfall -- Vehicle Image Classification Based on Edge: Features and Distances Comparison. Improved BTC Algorithm for Gray Scale Images Using K-Means Quad Clustering -- Optimization of a Neural Network for Computer Vision Based Fall Detection with Fixed-Point Arithmetic -- Customer Relationship Management Using Partial Focus Feature Reduction -- An Automated System for the Grading of Diabetic Maculopathy in Fundus Images -- An Iterative Method for a Class of Generalized Global Dynamical System Involving Fuzzy Mappings in Hilbert Spaces -- Estimation of Missing Precipitation Records Using Modular Artificial Neural Networks -- Office Employees Authentication Based on E-exam Techniques -- Obtaining Single Document Summaries Using Latent Dirichlet Allocation -- Object Recognition Using Sparse Representation of Overcomplete Dictionary -- PEAQ Compatible Audio Quality Estimation Using Computational Auditory Model.- A System for Offline Character Recognition Using Auto-encoder Networks -- TrafficS: A Behavior-Based Network Traffic Classification Benchmark System with Traffic Sampling Functionality -- Harmony Search with Multi-Parent Crossover for Solving IEEE-CEC2011 Competition Problems -- New Intelligent Interactive Automated Systems for Design of Machine Elements and Assemblies.- Neural Networks Based Aerial Images Segmentation Method -- Frontal Cortex Neural Activities Shift Cognitive Resources Away from Facial Activities in Real-Time Problem Solving -- Implement Real-Time Polyphonic Pitch Detection and Feedback System for the Melodic Instrument Player -- Classification of Interview Sheets Using Self-Organizing Maps for Determination of Ophthalmic Examinations -- Sound-Based Ranging System in Greenhouse Environment with Multipath Effect Compensation Using Artificial Neural Network -- Multimedia Educational Content for Saudi Deaf -- Grasping Region Identification in Novel Objects Using Microsoft Kinect -- Annotating Words Using WordNet Semantic Glosses -- Identification of Moving Vehicle Trajectory Using Manifold Learning -- Approaches for the Detection of the Keywords in Spoken Documents Application for the Field of E-Libraries.- Fast Affine Invariant Shape Matching from 3D Images Based on the Distance Association Map and the Genetic Algorithm -- Sparse Gradient-Based Direct Policy Search -- Application of Sampling Theory to Forecast Ozone by Neural Network -- Application of Genetic Neural Networks for Modeling of Active Devices -- Displacement Prediction Model of Landslide Based on Ensemble of Extreme Learning Machine -- Effective Handwri.
Keywords: Computers; Artificial intelligence; Pattern recognition; Data mining; Computer simulation; Optical data processing; Computation by Abstract Devices; Artificial Intelligence; Pattern Recognition; Data Mining and Knowledge Discovery; Simulation and Modeling; Image Processing and Computer Vision